Carmen Bernand: “Connected stories / Stories on the margins” (2009)
On March 27 and 28, 2009, the Department of Humanities of the EAFIT University invited Franco-Argentine professor Carmen Bernand to give a series of lectures that were presented in the framework of the third version of the International Seminar on Society